Taksonomi Mangga Budidaya Indonesia dalam Praktik - , Fitmawati; Alex Hartana; Bambang S. Purwoko (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2009)
The classification of cultivated plants should meet two approaches namely the botanical (classifying based on essential systematic plant characters) and the practical approach (clustering based on the analysis of commercial properties). This study analyzed taxonomy of mango cultivars grown in Indonesia based on morphology and agronomy characters. It obtained 84 recognizable cultivars.They are grouped into eigth main cultivar-groups (e.g. Berem, Madu, Gedong, Golek, Bapang, Arumanis, Kepodang, and Kebo) and eigthteen cultivar-groups. The 'Lalijiwo' cultivars synonym with 'Thaber', 'Tabar', 'Gurih' whereas 'Arummanis' synonim with 'Gadung'. Meanwhile, the cultivar 'Kates277' which is a member of Golek cultivar main group is homonim with the cultivar 'Kates' in Arummanis cultivars main group. Furthermore, the cultivar Nanas93 (one of Madu main group cultivar) that different with the cultivar 'Nanas71' which is categorized as member of Bapang main cultivar group. Key words: Taxonomy of cultivated plant, Indonesian mango, morphology, agronomy characters